Derivatization of Levoglucosan for Compound-Specific δ13C Analysis by Gas Chromatography/Combustion/Isotope Ratio Mass Spectrometry. (26th July 2020) - Zhang, Dongling; Swe Aung, Swe; Han, Yong; Zhang, Yanlin; Chen, Yingjun; Li, Hongli; Yu, Feifei; Wang, Yangjun; Feng, Jialiang; Wang, Wu
Abstract : Levoglucosan is a thermal decomposition product of cellulose in particulate matter. δ 13 C value of levoglucosan could be used in studying the combustion mechanisms and chemical pathways. In order to introduce a minimum number of carbon atoms, based on the stereostructure of levoglucosan, a two-step derivatization method with methylboronic acid and MSTFA was developed and carefully optimized. The recommended reaction temperature is 70°C; the reaction time is 60 min for MBA and 120 min for MSTFA derivatization; and the molar ratio of levoglucosan : MBA : MSTFA is 1 : 1: 100 and 1 : 1: 120 and the reagent volume ratio of MSTFA : pyridine is between 1 : 3 and 1 : 4. The developed method achieved excellent reproducibility and high accuracy. The differences in the carbon isotopic compositions of the target boronate trimethysilylated derivative between the measured and calculated ranged from 0.09 to 0.36‰. The standard deviation of measured δ 13 C value of levoglucosan was between 0.22 and 0.48‰. The method was applied to particle samples collected from the combustion of cellulose at four different temperatures. δ 13 C values of levoglucosan in particle samples generated from a self-made combustion setup suggesting that combustion temperature play a little role on isotope fractionation of levoglucosan, although 13 C enriched in levoglucosan during the combustion process.